A Good Example of Stunting Reduction at Districts/Cities in Indonesia: Secondary Data Study - Fentiana, Nina; Sudiarti, Trini; Ginting, Daniel; Suharto, Suharto (Poltekkes Kemenkes Palu, 2025)
Background: The 2025-2029 NMDP targets a reduction in stunting of 14.4% in 2029 from a baseline of 18.8% in 2025. This means that stunting must be reduced by 4.4% over 4 years, or approximately 1.1% per year. Indonesia has only managed to reduce stunting by 0.1% per year. This research aims to identify best practices, provide policy insights, or analyze success factors. Methods: The study processed aggregate data at the district/city level from Basic Health Research 2018, Susenas 2018 and Gross Regional Domestic Product (PDRB) data from BPS 2018 with a cross-sectional design. Stunting was measured in children aged 0-23 months using standardized value (Z-score) using WHO Anthro 2018. Other data variables are presented in percentages. Correlation tests and path analysis were used to see the direct and indirect relationships of various risk factors to stunting. Results: There is a significant relationship between access to food and the prevalence of stunting at the district/city level (p-value <0.05; r-value = 0.19). Pregnancy check-ups (path coefficient = -0.29) and access to food (path coefficient = -0.31) have a significant direct contribution to the prevalence of stunting at the district/city level. Conclusion: Research findings state that pregnancy checks according to regulations and access to food are risk factors for stunting that have a major impact on reducing stunting in districts/cities. In low and medium categories of stunting, the government needs to pay attention to the disparity in the percentage of nutritional services for these two factors, along with other factors that are already running.